Pengungkapan Environmental, Social, and Governance Disclosure Terhadap Volatilitas Harga Saham Syariah Dimoderasikan oleh Likuiditas - Ardianto, Ferdi; Sukardi, Agung Slamet (Jurnal Ilmiah Ekonomi Islam, 2024)
This study examines the effect of ESG (Environmental, Social, and Governance) factors on the volatility of Islamic stock prices in the Jakarta Islamic Index (JII). The aim is to understand how sharia compliance, sustainability, social impact, and corporate responsibility affect sharia stock price fluctuations, as well as attract Muslim investors and potential investors to sharia instruments. Secondary data from JII companies for the 2021-2023 period was analyzed using purposive sampling method. The results show that ESG has a significant negative effect on Islamic stock price volatility. This suggests that companies with good ESG practices tend to be more stable and attractive to investors. However, this study also found that liquidity does not moderate the relationship between ESG and Islamic share price volatility. This means that the liquidity level of the company does not affect the negative effect of ESG on stock price volatility. This study has limitations, such as the use of JII data and a short research period. In the future, further research could consider ESG scores from various sources and compare the Islamic and conventional stock markets to understand the differences in characteristics and dynamics, as well as the role of ESG in both markets.